Analysis of Risk Factors for The Severity of Hyaline Membrane Disease in Preterm Infants Based on Modality Chest X-Ray - Aulia Kusuma Dewi; Farah Hendara Ningrum; Adhie Nur Radityo Suswihardhyono; Lydia Widyastuti Setjadiningrat Kuntjoro (RSUP Dr. Kariadi, 2025)
BACKGROUND : Hyaline membrane disease is one of the leading causes of morbidity and mortality in premature infants. Chest X-ray examination can significantly improve the diagnosis of hyaline membrane disease. AIMS : This study aims to examine the relationship between risk factors and the severity of hyaline membrane disease using chest X-ray modalities. METHOD : An analytic observational study with a cross sectional and retrospective approach was conducted. Consecutive sampling of 30 preterm infants’s medical records and thoracic X-ray at Dr. Kariadi Hospital Semarang was used. Data collection was carried out from April to July 2023. Statistical tests included the Contingency Coefficient Correlation Test and Intraclass Correlation Coefficient (ICC). RESULT : Findings indicate that HMD severity is associated with lower birth weights (p = 0.020; r = 0.392); gestational ages (p = 0.011; r = 0.420) and maternal hypertension (p = 0.013; r = 0.414). Preeclampsia, delivery method, and gender not significantly related to the HMD severity (p>0.05). CONCLUSION : Infant birth weight, gestational age, and maternal hypertension are significantly associated with the severity of hyalin membrane disease.